Defect modification engineering on a laminar MoS2 film for optimizing thermoelectric properties. Issue 6 (4th February 2020) - Ding, Wenjun; Li, Xia; Jiang, Fengxing; Liu, Peng; Liu, Peipei; Zhu, Shuai; Zhang, Ge; Liu, Congcong; Xu, Jingkun
Abstract : A high carrier mobility and high Seebeck coefficient laminar MoS2 –Cu film was obtained via effective defect modification. Abstract : Two-dimensional (2D) transition-metal dichalcogenide (TMD) films have emerged as promising semiconducting materials for electronic and optoelectronic applications. However, a defect region, such as gap or void areas between the edges of the nanosheets originating from the layer-by-layer assembly of 2D nanosheets, is often inevitably present in laminar TMD films and strongly affects the semiconductor properties. In this work, we developed a defect modification strategy to patch the gap regions in molybdenum disulfide (MoS2 ) film for optimizing its thermoelectric performance. The defect regions can be bridged through the nanoconfinement electrostatic force between the surface anisotropic MoS2 nanosheets and inserted copper, leading to a MoS2 –Cu lateral heterostructure. Compared with the MoS2 film, the carrier mobility of the modified MoS2 film increased 15 times, resulting in a high Seebeck coefficient of 159.4 μV K −1 at room temperature. In addition, the thermoelectric stability of MoS2 films can be improved simultaneously. Our results provide a new concept of microstructure regulation on laminar TMD films to improve thermoelectric performances and will promote 2D laminar films with potential applications in other semiconductor fields.